2018
DOI: 10.1029/2018jd028396
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Water Physiological Integration and its Ecological Significance for Populus euphratica Young Ramets in an Extremely Drought Environment

Abstract: Water physiological integration plays an important role and has profound effects on the population renewal and expansion of clonal plants. This work discussed the spatial distribution architecture, water sources, water physiological integration, and the ecological significance of Populus euphratica young ramets in an extremely drought environment based on field investigation, stable isotope technology, and eco‐physiological experiments. The spatial distribution architecture of P. euphratica young ramets assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…All clonal fragments must adopt a cost-benefit tradeoff strategy when the costs outweigh the benefits of resource translocation (Wang et al, 2014;Zhang et al, 2020). Results showed that this cost-benefit tradeoff strategy occurred when the spacer length was approximately 30 cm (Figure 3), which was different from the results for Populus euphratica (20-30 m) (Zhu et al, 2018), Halophila stipulacea (2.7 cm), and Cymodocea nodosa (81 cm) (Marba et al, 2002). This may be due to differences in species of clonal plants (D'Hertefeldt et al, 2014;You et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…All clonal fragments must adopt a cost-benefit tradeoff strategy when the costs outweigh the benefits of resource translocation (Wang et al, 2014;Zhang et al, 2020). Results showed that this cost-benefit tradeoff strategy occurred when the spacer length was approximately 30 cm (Figure 3), which was different from the results for Populus euphratica (20-30 m) (Zhu et al, 2018), Halophila stipulacea (2.7 cm), and Cymodocea nodosa (81 cm) (Marba et al, 2002). This may be due to differences in species of clonal plants (D'Hertefeldt et al, 2014;You et al, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Differences in spacer length may affect the energy required for resource translocation and limit the intensity of clonal integration (Liu et al, 2004;Li et al, 2008;Yu et al, 2020). Previous studies have shown that the benefits of the physiological integration of water in a clonal fragment of Indocalamus decorus and Populus euphratica decrease when the spacer length increases (Hu et al, 2015;Zhu et al, 2018). In addition, the ramet number can also lead to differences in the sizes of clonal fragments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the increased precipitation brought an enhanced carbon sequestration for the desert-grassland ecosystem in Inner Mongolia (Zhang et al, 2019). The characteristics of water physiological integration to young ramets of Populus euphratica Oliv., which is important in maintaining oases in the desert riparian forest ecosystem, was found to be characterized by an acropetally flow by combining field survey and experiment (Zhu et al, 2018). Finally, the relationships between the flooding of 413 Australian catchments and larger-scale climate indices such as the El Niño-Southern Oscillation were investigated (Liu, Zhang, et al, 2018).…”
Section: Understanding the Key Processes Of Water-soil-air-plant-huma...mentioning
confidence: 99%
“…As established P. euphratica trees are completely dependent on groundwater and as this species is capable of forming extensive clones, the question of the water transport capacity through the spacers that connect a ramet with its 'parent' plant arises. Recently, Zhu et al (2018) conducted on-site measurements of the water flow through P. euphratica spacers, but only considered the connections between small 'daughter ramets' (<1.5 m high, <3.0 cm stem diameter) with their 'parent' plant and did not include mature tree ramets in their study. Nevertheless, they found a significantly higher water use in the ramets compared to that of seedlings.…”
Section: Introductionmentioning
confidence: 99%